2007
DOI: 10.1007/s00427-007-0183-y
|View full text |Cite
|
Sign up to set email alerts
|

Contactin 1 knockdown in the hindbrain induces abnormal development of the trigeminal sensory nerve in Xenopus embryos

Abstract: In Xenopus tailbud embryos, the mandibular branch of trigeminal sensory nerve has a transient pathway innervating the cement gland. This pathway is settled by pioneer neurons in the trigeminal ganglion and along which extend later-growing axons from the trigeminal ganglion and the hindbrain. Axons in this branch express a neuronal recognition molecule, Contactin 1, from the initial stage of its outgrowth in early tailbud embryos and form a tightly joined, strongly Contactin 1-positive fascicle in the later sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These data suggest that Tag1 may help maintain the integrity of the ganglion, which is consistent with its potential to interact homophilically and heterophilically with other cell adhesion molecules (Brummendorf and Rathjen, 1996). Tg afferent axons are defasciculated following ectopic Slit or neurotrophin expression (Yeo et al, 2004; and Ozdinler et al, 2004), and Tg peripheral axons are defasciculated following contactin1 knockdown (Fujita and Nagata, 2007), but our observations are the first report of disruption of Tg cell body clustering. Other cell types expressing tag1 such as the nucMLF in the midbrain and Rohon–Beard sensory neurons in the spinal cord also exhibit specific defects in axon outgrowth in tag1 morphants (Liu and Halloran, 2005; and Wolman et al, 2008).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…These data suggest that Tag1 may help maintain the integrity of the ganglion, which is consistent with its potential to interact homophilically and heterophilically with other cell adhesion molecules (Brummendorf and Rathjen, 1996). Tg afferent axons are defasciculated following ectopic Slit or neurotrophin expression (Yeo et al, 2004; and Ozdinler et al, 2004), and Tg peripheral axons are defasciculated following contactin1 knockdown (Fujita and Nagata, 2007), but our observations are the first report of disruption of Tg cell body clustering. Other cell types expressing tag1 such as the nucMLF in the midbrain and Rohon–Beard sensory neurons in the spinal cord also exhibit specific defects in axon outgrowth in tag1 morphants (Liu and Halloran, 2005; and Wolman et al, 2008).…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, migration of all FBMNs is blocked in tag1 morphants, suggesting that tag1 knockdown blocks migration of the earliest-migrating (“pioneer”) FBMNs (expressing Tag1 protein), which in turn may regulate the migration of later-migrating (“follower”) FBMNs (not expressing Tag1 protein). This putative non-autonomous effect on “follower” FBMNs may 1) be mediated by heterophilic interactions between Tag1 on “pioneer” FBMNs and cell adhesion molecules like NrCAM or L1/NgCAM (Brummendorf and Rathjen, 1996) or Contactin1 (Fujita and Nagata, 2007) on “follower” FBMNs, or 2) be independent of Tag1 function.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these in vitro observations, in vivo studies reveal a critical role of CNTN-1 in axon guidance and synapse formation [8][10]. Knockdown of CNTN-1 in Xenopus embroys resulted in misguidance and the defasciculation of the trigeminal nerve axons [11]. Whereas, mice deficient in CNTN-1 die in a few weeks due to severe ataxia [4], [8].…”
Section: Introductionmentioning
confidence: 70%
“…The expression and function of CNTN1 has been generally characterized in the central nervous system, and is involved in the regulation of neurite growth, synapse formation, fasciculation, and myelin organization. 13 15 Additionally, mutations in the CNTN1 gene can cause a familial type of lethal congenital myopathy. 16 Increasing numbers of studies have demonstrated that CNTN1 is altered in several cancers, including lung, esophageal, and gastric cancer.…”
Section: Discussionmentioning
confidence: 99%